PENERAPAN SENAM BAYI UNTUK MENINGKATKAN PERKEMBANGAN MOTORIK BAYI 3-12 BULAN DI PMB VITRI SUZANTI - Nurbaity; SUNDARI, DONA TRI (Jurnal Kesehatan dan Pembangunan, 2025)
Baby gymnastics is one of the effective stimulations to support the motor development of infants during growth. This activity involves simple movements that are specifically designed to stimulate the muscles, coordination, and motor skills of infants, both gross and fine motor skills. This study aims to analyze the effectiveness of baby gymnastics in improving motor development in infants aged 3-12 months. The purpose of this study was to determine the relationship between Baby Gymnastics and Infant Motor Development in PMB 2024. This study used a quantitative descriptive method with a cross-sectional approach with a sample size of 16 people. The results of the study showed that 54.5% of infants who did baby gymnastics experienced good motor development, and 45.5% of infants who did not do baby gymnastics did not experience infant motor development. The results obtained from the bivariate analysis of the chi-square statistical test showed that the p value = 0.588> a 0.05. The conclusion is that there is no relationship between infant gymnastics and infant motor development at PMB Vitri Suzanti Palembang in 2024. Suggestions are expected for midwifery students and health workers to provide IEC through counseling or education about the benefits of infant gymnastics to improve infant motor development for the community and it is expected for those who participate in infant gymnastics to always consult with health workers regarding changes that occur after doing infant gymnastics so that if there are abnormalities, they can be addressed immediately.